Charging station to provide greater autonomy to the Robobo - Vizcaíno-Delgado, Mónica (2021)
Robobo is a mobile robotic platform developed by Universidade da Coruña’s MINT company. It is currently used as a tool for learning and benefit from the different advantages of autonomous and collaborative robotics at schools and investigation centers, it also can be found on the market as an educational package that includes four units.  However, Robobo’s performance lacks on an autonomous, automated, homogeneous or simultaneous recharging process. Therefore, this article treats the importance and the design of a first electromechanical prototype of a charging station as an approach to obtain an autonomous and simultaneous charging cycle of up to four Robobo mobile platforms.